M5STACK ELECTRONIC BLUEPRINTS a practical approach for building interactive electronic controllers and IoT devices - Wilcher, Don (Packt Publishing Ltd., 2023)
Acquire hands-on knowledge and technical skills for designing and developing aesthetically appealing, interactive devices using ESP32, Arduino, and SNAP circuits with M5Stack Core Key Features Learn ESP32 microcontroller and M5Stack Core development platform with hands-on projects Create aesthetically appealing visuals for technology engagement using the M5Stack Core device Build interactive devices using Arduino and SNAP circuits with the M5Stack Core development platform Book Description As an embedded systems developer or an IoT developer, you can often face challenges in maintaining focus on prototyping a product concept while using a specific high-level programming language for implementation. To overcome these challenges, the M5Stack Core platform uses an ESP32 microcontroller and block code that allows you to focus on product creation and application instead of the high-level programming language. M5Stack Electronics Blueprints presents various design and prototyping approaches as well as UI layout and electronics interfacing techniques that will help you to become skilled in developing useful products effectively. This book takes you through a hands-on journey for a better understanding of the ESP32 microcontroller and the M5Stack Core's architecture. You'll delve into M5Stack Core topics such as electronic units, light, sound, motion devices, interfacing circuits, SNAP circuit kits, Arduino applications, and building Bluetooth and Wi-Fi IoT devices. Further, you'll explore various M5Stack core applications using a project-based learning method, including the fascinating 32-bit microcontroller device technology. By the end of this book, you'll be able to design and build interactive, portable electronic controllers, IoT, and wearable devices using the M5Stack Core. What you will learn Design user interfaces using no-code/low code programming languages Prototype electronic controllers for audio alarms swiftly Wire an M5Stack Core 2 to an Arduino Uno or equivalent to build a touch control relay controller Prototype Bluetooth IoT controllers efficiently Build and code Wi-Fi sniffers and scanner gadgets Prototype wearable devices with ease Create ESP32 applications using system block diagram design Build a DC motor controller operated by a M5Stack Core unit Who this book is for This book is for practicing embedded systems and IoT developers, electronics and automation technicians, STEM technical educators, students, and hobbyists looking to learn about the ESP32 microcontroller and M5Stack technologies. There is no prerequisite - apart from a desire to learn about ESP32-based electronics and interactive devices, then this book is for you.